Sustainable Tourism Practices in Nepal and Its Challenges - Khanal, Ramesh (SMC Journal of Sociology, 2025)
This piece of writing delves into the contemporary status of sustainable tourism practices within the Mount Everest region, emphasizing ecological conservation, cultural preservation, and revenue generation while pinpointing significant obstacles. A study was conducted in Solukhumbu district utilizing a purposive sampling technique to gather data from 23 individuals, comprising trekking guides, hotel proprietors, porters, local community members, ward committee personnel, and tourists. The results underscore critical deficiencies in sustainability practices across three dimensions. Environmentally, tourism stakeholders exhibit limited awareness and insufficient conservation efforts, exacerbated by inadequate waste management. Socio-culturally, the absence of advocacy for indigenous culture by local stakeholders and a lack of understanding of local traditions among guides jeopardize cultural preservation. Economically, the seasonal character of tourism engenders income volatility, compelling residents to pursue alternative livelihoods. This has resulted in migration to urban centers or abroad, further intensifying income disparity within the community. Challenges encompass ineffective environmental strategies, feeble cultural promotion, and inequalities in income distribution. Tackling these challenges necessitates collaborative endeavors among stakeholders to enact responsible tourism practices. Fortifying legal frameworks, advancing cultural education, and empowering local communities are vital to augment sustainability and equitable advantages in the tourism sector of the Everest region.